A 16-year-old Girl with Morquio Syndrome: A Case Report (BIRDEM Medical Journal, 2018)
Morquio syndrome is a rare autosomal recessive disorder of mucopolysaccharide metabolism, also called mucopolysaccharidosis type IV. We report a case of Morquio syndrome in a16-year- old girl of normal intelligence, who got herself admitted in Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. The patient had short stature and skeletal deformity and she belonged to a non-consanguineous marriage of her parents. She was diagnosed on the basis of clinical features, typical radiological changes and positive urinary mucopolysaccharide screening test.Birdem Med J 2018; 8(3): 266-269